Role of Farm Forestry in Soil & Water Conservation - Madan, U.S. (Journal of Soil and Water Conservation, 2022)
Civilization has sprung up from forests, but it has been unfortunate that man has cleared the forests indiscriminately. Today, in India, forests are reduced to about less than 22 percent of the total area against a goal of 33 percent (60% in the hills and 20% in the plains) laid down in the National Forest Policy of India of 1952. Due to the vast clearance and ruthless destruction_ of the forests tremendous damage has been caused in India as a result of which we are having devastating floods, advancing deserts, soil erosion, irregular rainfall, and scarcity of food, fuel and fodder.India is predominantly agricultural country. Sound agricultural practices are not possible in the absence of forests. Destruction of forest has resulted in poor cultivation due to soil erosion, and rapid runoff of water creating both floods and drought. Forest is referred as 'Mother of Agriculture'.